Weight loss and surface roughness of hard chairside reline resins after toothbrushing: Influence of postpolymerization treatments - Mendonça, Márcio José; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (My University, 2006)
Purpose: To evaluate the effect of 2 postpolymerization treatments on toothbrushing wear (weight loss) and surface roughness of 3 autopolymerized reline resins-Duraliner II (D) (Reliance Dental), Kooliner (K) (Coe Laboratories), and Tokuso Rebase Fast (T) (Tokuyama Dental)-and 1 heat-polymerized resin, Lucitone 550 (L) (Dentsply International). Materials and Methods: Specimens (40 x 10 x 2mm) of each material (n = 24) were prepared and divided into 3 groups: control (no postpolymerization treatment); water bath (immersion in water at 55°C); and microwave (microwave irradiation). Specimens were dried until constant weight was achieved and the surface roughness (Ra) was measured. Tests were performed in a toothbrush machine using 20,000 strokes of brushing at a weight of 200 g, with the specimens immersed in 1:1 dentifrice/water slurry. Specimens were reconditioned to constant weight and the weight loss (mg) and surface roughness were evaluated. Data were analyzed by 2-way analysis of variance and followed by Tukey test (α = .05). Results: In the control group, the weight loss of materials D and T was lower (P < .05) than that of L. No differences among materials were found after postpolymerization treatments (P > .05). The weight loss of material T (control = 0.5 mg) was significantly increased (P < .05) after postpolymerization treatments (water bath = 1.9 mg; microwave = 1.8 mg). For materials K and T, the toothbrushed surface roughness was higher (P < .05) after microwave and waterbath postpolymerization treatments. Material L showed increased surface roughness after microwave postpolymerization treatment. Conclusion: The toothbrushing wear resistance of L was not superior to the reline resins. The postpolymerization treatments did not improve the toothbrushing wear resistance of the materials and produced an increased surface roughness for materials L, K, and T.
Keywords: acrylic acid resin; biomedical and dental materials; duraliner II; kooliner; Lucitone; methacrylic acid derivative; polymer; Tokuso Rebase Fast; toothpaste; water; chemistry; comparative study; denture; human; instrumentation; materials testing; microwave radiation; radiation exposure; surface property; tooth brushing; Acrylic Resins; Dental Materials; Dentifrices; Denture Bases; Denture Liners; Denture Rebasing; Humans; Materials Testing; Methacrylates; Microwaves; Polymers; Surface Properties; Toothbrushing; Water